PENELUSURAN ALUR PIKIR DIBALIK ISTILAH KONSEP DASAR DAN TEMA PADA TUGAS AKHIR ARSITEKTUR UNUD - Alam Paturusi, Syamsul (Jurnal Natah, 2005)
Basic concept and thema of the final project in Departmenty of Architecure Unud have already been discours academic. The difference of opinions occur because the matters pertaining to meaning in confusion, deviate from scientific thinking process. This paper will give the simple thinking: to purpose on process that the cronological of treasuring behind the both meaning can give comfrehension about the meaning in fact (essence and function) and scientific logically.